Learning and Earning in Vacationland: Promoting Education and Economic Opportunity in Maine - Carnevale, Anthony; Desrochers, Donna (Maine Policy Review, 2002)
Technological innovation, globalization and other economic forces together shape the structure of jobs and the way we work. Such forces have gained momentum over the last 40 years with the advent of a new economy that is increasingly reliant on skilled workers with a postsecondary education. This trend is evident in all sectors of Maine’s economy. In this article, Carnevale and Desrochers show where the jobs are in Maine and how the education attainment of those who hold such jobs has changed over the last 40 years. They look at where jobs will be in the future and the skills that employers want. They project that the forces fueling the demand for college-educated workers today will continue to grow, along with the income divide between those who have some postsecondary education and those who do not.
Keywords: Maine; education; job skills